2016
DOI: 10.5194/bg-13-467-2016
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal contrasts of sedimentary organic matter in floodplain lakes of the central Amazon basin

Abstract: Abstract. In this study, we investigated the seasonal and spatial pattern of sedimentary organic matter (SOM) in five floodplain lakes of the central Amazon basin (Cabaliana, Janauaca, Canaçari, Mirituba and Curuai) which have different morphologies, hydrodynamics and vegetation coverages. Surface sediments were collected in four hydrological seasons: low water (LW), rising water (RW), high water (HW) and falling water (FW) in 2009 and 2010. We investigated commonly used bulk geochemical tracers such as the C … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 65 publications
0
41
0
2
Order By: Relevance
“…In order to evaluate the Madre de Dios data in a broader context, we compiled published lignin data from the Amazon River system [ Ertel et al ., ; Hedges et al ., , ; Farella et al ., ; Kastner and Goñi , ; Bernardes et al ., ; Aufdenkampe et al ., ; Ward et al ., , ; Sobrinho et al ., ]. As noted previously, FPOM (>0.1 or 0.45 µm and < 63 µm) and CPOM (>63 µm) in the Amazon River system have distinct lignin content (Figure a), with higher Λ lignin values in the CPOM.…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the Madre de Dios data in a broader context, we compiled published lignin data from the Amazon River system [ Ertel et al ., ; Hedges et al ., , ; Farella et al ., ; Kastner and Goñi , ; Bernardes et al ., ; Aufdenkampe et al ., ; Ward et al ., , ; Sobrinho et al ., ]. As noted previously, FPOM (>0.1 or 0.45 µm and < 63 µm) and CPOM (>63 µm) in the Amazon River system have distinct lignin content (Figure a), with higher Λ lignin values in the CPOM.…”
Section: Resultsmentioning
confidence: 99%
“…Organic matter (OM) in the floodplain lakes of the central Amazon basin may potentially be derived from: (1) terrestrial Andean clay-bound and refractory suspended particulate OM, which may be transferred to the floodplain lakes via the Solimões-Amazon and Madeira rivers; (2) nonflooded soils and litters of the Amazonian lowland forests (nonflooded forests), which is transferred to the floodplain lakes via local streams; (3) wetland soils (flooded forests) and litters (leaves, grasses, woods, etc. ), transferred to the floodplain lakes during the receding waters (falling water season) or the rainy season (RW season); (4) wetland aquatic and semi-aquatic macrophyte vegetation of the floodplain lakes; and (5) phytoplankton from the river or produced in the lake itself (Sobrinho et al 2016).…”
Section: Geochemical Measurementsmentioning
confidence: 99%
“…Due to the absence of random variations, we propose that a single overriding mechanism may be responsible for the observed trend. Most likely, an increased contribution of C 4 macrophytes to the soil OM is responsible for the progressively less negative values (Sobrinho et al 2016). This explanation would be supported by other studies in the central Amazon basin, which reported that the abundance of macrophytes in this lakes increases in open water lakes and floodplains (Victoria et al 1992;Martinelli et al 2003;Sobrinho et al 2016).…”
Section: Oc Content and Stable Carbon Isotope Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…During periods of intense rain and flooding, organic material is exported from catchments via leaching and runoff (Mayorga et al 2005;Ward et al 2013). Rivers within the Amazon Basin carry megatons of organic material, a large portion of which is deposited on the floodplains and in floodplain lakes when the seasonal flooding subsides (Hedges et al 1986;Aalto et al 2003;Moreira-Turcq et al 2004;Mortillaro et al 2012;Moreira-Turcq et al 2013;Sobrinho et al 2016). As a result, the floodplains and their lakes may be significant carbon sinks in the Amazon Basin because of slow organic material decomposition in mostly anaerobic sediments (Mertes 1994;Hamilton et al 2002;Dong et al 2012;Ferland et al 2014).…”
mentioning
confidence: 99%